MODERN ACCOUNTING METHODS FOR GOVERNMENTAL UNITS. - Herbert, Leo (The Accounting Review, 1956)
Abstract The industrial revolution with its division of labor, its competition, and its profit motive demanded forms of measurement which could not be found in the conventional single-entry or simple double-entry bookkeeping system. Stockholders, workers, and management demanded reports of operations and financial information on a current basis which had not been available before then. Governmental accounting has a great many basic concepts found in industrial accounting, although some of the major principles are completely different. In industrial accounting the measurement of profits is the deciding factor for a great many of the basic principles. Matching of costs and revenues probably is considered the fundamental concept of industrial accounting. No such concept exists in governmental accounting. Usually, revenues and expenditures do not have a direct accounting relationship in governmental administration. Most governmental units have a great many operational activities. One set of combined records is not sufficient to analyze these activities. Governmental fund accounting for each of these various operational activities has no counterpart in industrial accounting.